Respuesta :

Answer:

  (x, y) = (-3, 3)

Step-by-step explanation:

You can add these two equations together to cancel the x terms:

  (3x +2y) +(-3x +y) = (-3) +(12)

  3y = 9 . . . . . . . . simplify

  y = 3 . . . . . . . . . divide by 3

__

Substituting for y in the second equation gives ...

  -3x +3 = 12

  -3x = 9 . . . . . subtract 3

  x = -3 . . . . . . divide by -3

The solution is (x, y) = (-3, 3).

_____

The solution can be found quickly and easily using a graphing calculator.

Ver imagen sqdancefan
ACCESS MORE